Seeing God Through African Minds - Pratt, T.K.A. (University of Ghana, 2011)
Africa had been referred to as the Dark Continent for several reasons prior to the era of expeditions which opened the continent up. European Anthropologists formulated several ideas about the continent and its peoples; most of which were derogatory, describing the African in the primitive stage as uncivilized backward and lacking any sense of decency. Before the advent of Missionary activities Africa was awash with Traditional Religious activities which the Missionaries found unacceptable and unworthy. Current African intellectuals have, since the 1950, made attempts to redeem Africa‟s natural glories and to place Africa on the international scene by making worthy contributions in all spheres of academic endeavours. Kwame Bediako‟s position on the indigenization of Christology in Africa with his references to other primal religions make his position remarkably authentic and convincing. His Christology identifies the essential areas in the African beliefs that are identical to western ideas; for example Odwira and its significances in line with the atoning blood of Jesus Christ in western thoughts; the blood of the Sacrificial Lamb which is shed to pacify and cleanse the African of all misdeeds is identified with the blood of Christ, the Sacrificial Lamb of God in Christian theology. Bediako‟s work is one of the several attempts in the area of religion and its comparative study. This is the inspiration behind this Dissertation.
Thesis (MA) - University of Ghana, 2011